Patch richness and shape complexity in Central Cebu protected landscape, Cebu Island, Philippines implications in environmental management - Bagarinao, Ricardo T. (2011)
The many advances in the field of landscape ecology allow the analysis of landscape structure vis-a-vis ecological processes. The study was conducted to measure patch richness (PR) and shape complexity (i.e. perimeter-to-area ratio, PAR) of the various patch classes in Central Cebu Protected Landscape (CCPL). CCPL is an important biodiversity zone in the Central Visayas region due to its high endemicity. Both patch richness and shape complexity indices were measured, and their implications on the management of the landscape were identified. CCPL consists of four patch classes, namely: perennial crops, annual crops, forests and built-up areas. Though annual crops showed the highest size in all patch types, the perennial crops have the highest patch number. PAR and PR values of forest patches indicate forest ecosystems in the landscape are highly fragmented and have greater edge than core area. If conservation objective is to protect endangered species from extinction, landscape management should focus on the establishment of connections among isolated forest patches. In particular, management should consider establishing patches with maximum core area if conservation is for the protection of core-dependent species.
Keywords: Landscape assessment -- Cebu; Environmental management -- Cebu; Biodiversity conservation -- Cebu